VALIDATION OF STRENGTH AND FLEXIBILITY OF SENGON (PARASERIANTHES FALCATARIA) BY EXPERIMENTAL TREE-PULLING TEST AND NUMERICAL SIMULATION - Dhelika, Radon (Journal of Applied Engineering Science, 2019)
Stability assessment of trees is considered important in urban areas to detect possible occurrence of tree failures that often result in disastrous damages. Tree-pulling test is a low-cost, well-known method that has been practiced by researchers and practitioners alike from several decades ago. From the method, a number of parameters related to the physical characteristics of the tree can be further derived. However, the tree-pulling test has only been widely practiced mostly for tree species in subtropical region, such as pines, spruces, and birches. In this paper, a tree-pulling test on sengon (Paraserianthes falcataria), a tree native to Indonesia is reported. Such a study is imperative as sengon is among the most commonly planted tree species in the urban areas of Indonesia and there have been alarming reports of falling sengon trees. Two kinds of tree-pulling test are conducted. i.e. destructive and non-destructive. From these experiments, the critical force that results in a breakage as well as the flexibility of sengon are obtained. Numerical simulations are also carried out. The results are compared and they show a good fit to the experimental data, justifying the assumed linearly elastic behavior.
Keywords: Paraserianthes falcataria; deflection; structural strength; tree-pulling test